Values, Education, Emotional Learning, and the Quest for Justice in Education - Al-Asfour, Ahoud,; Waghid, Yusef, (Comparative and International Education: Diversity of Voices ;, 2024)
Values, Education, Emotional Learning, and the Quest for Justice in Education explores emotional teaching-learning as it is cultivated based on teachers' and learners' attraction to reasonableness and emotions and can give rise to a plausible form of decoloniality or decolonisation in and through education. This volume argues that when the latter manifests, the democratic transformation of education might ensue. Put differently, decoloniality or decolonisation of education is a substantive way to look at the democratisation and, by implication, transformation of education and schooling. We invite our readers to engage with the meanings espoused throughout this book in the quest to cultivate a genuinely decolonial form of education in universities and schools, where values education should be enacted reasonably and emotively in such educational institutions. Teachers and learners cannot remain silent when oppressive and hegemonic forces of modernity continue to guide educational practices in institutions. Contributors are: Ahoud Alasfour, N'Dri Thérèse Assié-Lumumba, Emiliano Bosio, José Brás, Juan Carlos Rodriguez Camacho, Michael Cottrell, Lucimar Dantas, Amanda Fiore, Carla Galego, Maria Neves Gonçalves, Logan Govender, Beatriz Koppe, Sibonokuhle Ndlovu, Phefumula Nyoni, Adaobiagu Nnemdi Obiagu, Peter Oyewole, Theresa A. Papp, Martyn Reynolds, Kabini Sanga, V. Sucharita, Yusef Waghid and Emnet Tadesse Woldegiorgis.